1997
DOI: 10.1091/mbc.8.5.923
|View full text |Cite
|
Sign up to set email alerts
|

A folded protein can be transported across the chloroplast envelope and thylakoid membranes.

Abstract: Many thylakoid lumenal proteins are nuclear encoded, cytosolically synthesized, and reach their functional location after posttranslational targeting across two chloroplast envelope membranes and the thylakoid membrane via proteinaceous transport systems. To study whether these transmembrane transport machineries can translocate folded structures, we overexpressed the 17-kDa subunit of the oxygen-evolving complex of photosystem II (prOE17) that had been modified to contain a unique C-terminal cysteine. This al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
109
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(113 citation statements)
references
References 45 publications
4
109
0
Order By: Relevance
“…Export of folded proteins had only been demonstrated experimentally in vitro for the plant equivalent of Tat, the ⌬pH-dependent import system of thylakoids. Clark and Theg (15) showed that prefolded and chemically crosslinked BPTI could be imported into thylakoids when linked to the 17-kDa subunit of the oxygen-evolving complex of photosystem II (prOE17). However, BPTI is a very small protein (56 residues, 6.5 kDa) and therefore not typical of native Tat and ⌬pH substrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Export of folded proteins had only been demonstrated experimentally in vitro for the plant equivalent of Tat, the ⌬pH-dependent import system of thylakoids. Clark and Theg (15) showed that prefolded and chemically crosslinked BPTI could be imported into thylakoids when linked to the 17-kDa subunit of the oxygen-evolving complex of photosystem II (prOE17). However, BPTI is a very small protein (56 residues, 6.5 kDa) and therefore not typical of native Tat and ⌬pH substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Processes such as cofactor incorporation or the assembly of protein subunits hinge on the formation of secondary or tertiary structure. In vitro experiments in the thylakoid system have shown that: (i) bovine pancreatic trypsin inhibitor (BPTI) fused to a ⌬pH-dependent pathway precursor is transported into thylakoids, even when BPTI was permanently folded by using irreversible disulfide cross-linkers that prevented any unfolding during the translocation process (15); and (ii) dihydrofolate reductase (DHFR) bound to methotrexate, a ligand that greatly stabilizes the folded state of the protein, is specifically targeted to the thylakoid lumen by the ⌬pH-dependent pathway (16). However, BPTI and DHFR are significantly smaller (56 and 187 aa, respectively) than typical ⌬pH-dependent polypeptide substrates.…”
mentioning
confidence: 99%
“…1 and 2). Working in parallel with the well characterized Sec pathway, the Tat system uses an entirely different mechanism and has the unique ability to transport fully folded proteins across coupled membranes (3,4). In general, it appears to be used primarily for the transport of proteins that are either obliged to fold prior to translocation, or which fold too tightly or rapidly for the Sec system to handle.…”
mentioning
confidence: 99%
“…We also observed that the import reaction continued in these experiments for at least 30 min without slowing, and sometimes even longer. This is longer than that usually reported for in vitro import reactions (38,41), which may be due to our keeping the chloroplasts in complete darkness during the reaction, thereby avoiding the formation of potentially harmful reactive oxygen species. This phenomenon was not investigated further.…”
Section: Effect Of Inhibitors On Intrinsic Background Atpase Activitymentioning
confidence: 77%